Manajemen Peserta Didik dalam Pembinaan Perilaku Keberagamaan - Fery Diantoro (IAIN Ponorogo, 2018)
Religious behavior becomes an important point that is very fundamental to be owned by every student, because this is closely related to the attitudes and behaviors that will be demonstrated by students in their daily life. Therefore, the schools should be able to present good behavior and religious attitudes to students. Religious behavior coaching is the process of behavior formation, morality and character for students to stock the present and future life. Behavior coaching of students into the work domain of the student management. The school must manage the students well to create students that are in accordance with what has been expected and aspired. In this study using a descriptive qualitative approach, describe the student management in the religious behavior coaching in MTs Al-Burhan Watulimo. With the findings consists of students' orientation activities, the worship habituation, reading Al-Qur'an, scientific and Islamic studies, and guidance of discipline and character.يصبح السلوك الديني نقطة مهمة جدا أن تكون مملوكة من قبل كل المتعلم، لأن هذا يرتبط ارتباطا وثيقا المواقف والسلوكيات التي سيتم إثباتها من قبل المتعلمين في حياتهم اليومية. لذلك، ينبغي أن تكون المدرسة قادرة على تقديم السلوك الجيد والمواقف الدينية للمتعلمين. توجيه السلوك الديني هو عملية تشكيل السلوك والأخلاق والطابع للمتعلمين لتخزن الحياة الحالية والمستقبلية. توجيه سلوك المتعلمين في مجال عمل إدارة المتعلمين. يجب على المدرسة إدارة المتعلمين بشكل جيد لخلق المتعلمين التي تتوافق مع ما كان متوقعا وتطلعا. في هذه الدراسة استخدم المنهج الوصفي النوعي، وصف إدارة المتعلمين في السلوك الديني في المدرسة الثناوية